Pengaruh Leverage, Profitabilitas Dan Likuiditas Terhadap Nilai Perusahaan - M Yudha Pratama; Fitra Dharma (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This study aims to examine the effect of leverage, profitability, and liquidity on the value of the Company. in companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. In this study, the population used came from financial statement data of companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The method used is purposive sampling so that a sample of 140 data samples is obtained. The type of data used is secondary data. Data analysis using classical assumption test, multiple linear regression analysis, hypothesis test (t test and coefficient of determination). Testing is carried out using the help of the Software Statistical Product and Service Solution (SPSS) program. The results showed that leverage (DER) has a significant effect on company value, profitability (ROA) has a significant effect on company value, and liquidity (CR) has a significant effect on company value.